Pengaruh Konseling Individu Dengan Teknik Self Talk Positive Dalam Meningkatkan Percaya Diri Pada Pecandu Narkoba - Auliyo Dwi Putra; Lena Marianti; Abdur Razzaq (Journal of Society Counseling, 2023)
This study entitled "The Effect of Individual Counseling With Positive Self Talk Techniques in Increasing Confidence in Drug Addicts at Genesa Babel Foundation, Pangkal Pinang City". In overcoming the problems faced by drug addicts, the author uses the Self Talk Positive technique, this technique aims to motivate drug addicts to change. This study aims to first, determine the confidence of drug addicts when they just entered the Genesa Babel Foundation rehabilitation. Second, to find out the process of the Positive Self Talk technique at the Genesa Babel Foundation. Third, to find out the results of self - confidence after being given the Self Talk Positive technique. The type of this research is field research (field research). While the type of data used is quantitative data. The subjects of this study were 5 drug addicts. Sources of data taken in this study are primary and secondary data sources. The data were obtained by using the interview method, the observation method and the documentation method. Data analysis techniques quantitative data analysis consists of three stages, namely: data management, data analysis, and interpretation of data analysis. The design of this research is Pre-Experimental Designs. The researcher used a pretest and posttest design. The result of pretest calculation before following individual counseling with positive self talk technique was 29.50 and posttest after attending individual counseling with positive self talk technique increased to 59.00. The test obtained from the paired sample t test shows the value of tcount = 25,460 at degrees of freedom (df) 3, then compared with ttable 0.05 = 2,353 with the provision that the value of tcount is greater than ttable (25,460 > 2,353), and the value of Sig. (2-tailed) is 0.000 < 0.05 then Ha is accepted and Ho is rejected, so it can be concluded that individual counseling services with the Self Talk Positive technique can be used to increase self- confidence in drug addicts at the Genesa Babel Foundation, Pangkal Pinang City.